Curcumin Delivery on Metal–Organic Frameworks: The Effect of the Metal Center on Pharmacokinetics within the M‑MOF-74 Family - Lawson, Shane; Newport, Kyle; Pederniera, Neila; Rownaghi, Ali Asghar; Rezaei, Fateme (ACS applied bio materials, 2021)
Metal–organic frameworks (MOFs) have gained considerable attention as drug delivery platforms over the past decade owing to their tunable physiochemical properties, biodiversity, and capability to encapsulate sizable active compound loadings. Nevertheless, many fundamental properties pertaining to MOFs’ pharmacokinetic performances as drug carriers have been poorly investigated. One such property is the relationship between the MOF metal center solubility and drug release rate. In this study, we investigated this relationship within the M-MOF-74 family by impregnating 30 or 50 wt % curcumin on either Mg-, Ni-, Zn-, or Co-MOF-74. The drug delivery performance of the materials was assessed in phosphate buffered saline solution by high-performance liquid chromatography over a time period of 0–24 h. From these experiments, it was determined that the 30 wt % curcumin loading led to increased drug delivery and kinetics compared to the 50 wt % loading regardless of the metal center, as the lower drug concentration did not hinder diffusion from the MOF pores. As such, the optimal curcumin loading within the M-MOF-74 family was concluded to be greater than 30 wt % but less than 50 wt %. These experiments also revealed that using Mg-MOF-74 as a drug carrier produced a twofold enhancement in the release rate from 0.15 to 0.30 h1/2 compared to the other three metal centers, where Mg-MOF-74’s improved pharmacokinetics were attributed to the increased group II Mg solubility compared to Ni, Co, or Zn transition metals. On the basis of these findings, it was concluded that to promote rapid pharmacokinetics, it is essential to use MOFs with more soluble metal centers to promote dissolution of the nanocarrier. While this study focused on M-MOF-74, we expect that this conclusion has implications to other crystallites as well.